(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Introduction: The production of the analysis of the energy efficiency of the variants of the Energy Sources applied for driving in the rotation with the required frequency of the wheel motor units of electric locomotives and electric trains in the diagnostic position without disassembly of the bearings makes it possible to use the vibroacoustic diagnostic banks of the rotary units of the traction motors of locomotives with the best energy indicators. Two possible options of Power supplies are considered: a three-phase bridge rectification circuit controlled with a step-down transformer and a pulse converter that receives power from the network through an unmanaged three-phase bridge rectifier (Larionov Scheme) to drive the rotation with the required frequency of the wheel motor units of electric locomotives and electric trains in the bearing diagnostic position without disassembly. In both cases, it is assumed that the Power supplies receive electricity from a 380/220 V, 50 Hz network. A comparison of the proposed power supply options was made on the basis of an energy efficiency assessment. The power factor and the power loss in power supplies are used as energy efficiency criteria. A diagnostic power supply is offered. Materials and Methods: Analytical methods are used to determine the power loss in the transformer, the controlled three-phase thyristor rectifier, the unmanaged three-phase diode rectifier, the input filter of the pulse converter, the IGBT transistor and the reverse diode of the pulse converter. Results: the energy indicators were determined in tabular forms: power loss in the transformer, controlled three-phase thyristor rectifier, unmanaged three-phase diode rectifier, input filter of the pulse converter, IGBT transistor and reverse diode of the pulse converter. Based on the evaluation of the power indicators of the two variants of the power supply, it is concluded that it is appropriate to use a transformer-less circuit in the vibroacoustic diagnostic position of rotary units. Discussion: An energy-efficient power supply option for the non-disassembly vibroacoustic diagnostic position is proposed, which includes an unmanaged semiconductor rectifier and a pulse converter executed on an IGBT transistor. Conclusions: A diagnostic software has been developed for the pulse-controlled power supply selected according to the results of the calculations.